Percutaneous Tracheostomy in Critically Ill Patients - Servillo, Giuseppe; Pelosi, Paolo (Springer International Publishing : Imprint: Springer, 2016)
This book provides an up-to-date and comprehensive overview on percutaneous tracheostomy (PT) in critically ill patients. The various PT techniques that may be employed in the intensive care unit are fully described, with discussion of the available tracheostomy tubes and selection criteria and with clear evaluation of the risks and benefits of each procedure. A further individual chapter is devoted to the methods of airway management that may be used during PT. Detailed attention is also paid to medical and nursing management inside and outside hospital, to quality of life issues in tracheostomized patients, and to the problem of informed consent. The book concludes by addressing the need for standard guidelines. Percutaneous Tracheostomy in Critically Ill Patients will be an excellent source of information and guidance for novice and more experienced physicians working in intensive care units, operating rooms, and emergency departments as well as for those responsible for patient aftercare.  .